Evaluation of Structural Performance of Poroelastic Road Surfacing Pavement Subjected to Rolling–Truck Tire Loads. Issue 1 (2016) - Srirangam, S. K.; Anupam, K.; Casey, D.; Liu, X.; Kasbergen, C.; Scarpas, A.
Road traffic is a major source of noise pollution. Road authorities and pavement researchers have been trying to reduce this noise pollution by laying quieter pavement surfaces. Poroelastic road surfaces (PERS) have been found to be the most effective solution because they are very porous and elastic in nature compared with conventional dense asphalt surfaces. However, the structural performance of PERS pavement under heavy traffic loads is still unknown. The aim of this study was to determine the critical stresses experienced by PERS pavement under heavy loads applied by a wide-base truck tire. For this purpose, finite element (FE) simulations of a wide-base truck tire rolling over a PERS pavement system were performed for various material properties of PERS and adhesive layers, speeds, tire loads, and inflation pressures. From the FE model results, the critical stress envelopes were constructed by using the concept of stress invariants. Stress invariants represent normal and shear stresses that might cause the PERS layer to fail under the critical combination of material, loading, and operating variables and therefore act as design indicators. The FE results showed that the higher contact pressures and the lower material stiffness resulted in higher stress invariants. It was also determined that the stiffness of the adhesive layer influenced the response of the PERS layer. The current study demonstrated a robust methodology for assessing the performance of a thin PERS layer pavement system under rolling–truck tire operating conditions.